The Future Challenge of Education: Decoding the ‘Not My Fault’ Mindset in Generation Z - Mawarni, Anisa; Taufik, Agus; Ilfiandra, Ilfiandra; Faizal, Faizal (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
This study explores a growing challenge in education Generation Z students who exhibit academic buoyancy without demonstrating responsibility or acknowledging academic shortcomings. Using a qualitative approach with in-depth interviews, the research uncovers a prevalent “Not My Fault” mindset: students maintain confidence and motivation despite academic underperformance while externalizing blame and lacking self-awareness. The findings reveal that peer influence, digital culture, and a surface-level academic environment contribute to the illusion of resilience. These students often equate confidence with competence, masking deeper issues of disengagement and poor self-regulation. The study also highlights the role of educational culture in reinforcing passive learning attitudes, where critical thinking and self-reflection are rarely emphasized. This paradox presents an emerging and urgent challenge for educators: how to develop future-ready learners who are not only confident, but also critically aware and accountable for their growth. The insights from this research can inform the design of more adaptive, values-based educational strategies to support both emotional development and authentic academic progress.